Effects of Sidestep Exercise with Elastic Bands on Multidirectional Speed Abilities and Navicular Drop in Young Male Football Players: A Randomized Cross-Over Trial - Juan L. Núñez-González; Oliver Gonzalo-Skok; Manuel J. García; Fernando Hernández Abad; Francisco J. Núñez (Applied Sciences)
The current study aimed to assess the effect of including the lateral-step or sidestep exercise with elastic bands on multidirectional speed abilities (linear, change of direction, and curve sprinting) and navicular drop and to know the impact of navicular drop changes on multidirectional sprinting changes in young male football players. Thirty-two young male football players (age: 14.7 ± 0.82) were randomly divided into group A (n = 16) or group B (n = 16). Using a crossover design trial (ABBA), a group performed three sets of six repetitions per side in the lateral-step exercise with elastic bands attached in a low vector, three days per week, plus their regular training sessions, while the other continued with their regular football training sessions during the first 3 weeks, changing the role during the next 3 weeks of the intervention. Pre-intervention and three and six weeks after the beginning of the intervention, a navicular drop test, a 10 m linear sprint test, a multiple change of direction test (V-cut), and a curvilinear sprinting test were assessed. The sidestep exercise with elastic bands significantly improved the ability to sprint multidirectionally in only three weeks of training (p < 0.05, n2 = 0.56 to 0.74), and there was a trend in the impact of multidirectional sprinting performance through those changes reported in the navicular drop test (r = −0.23 to 0.45).